PENETAPAN KADAR AKRILAMIDA DALAM MAKANAN KAKI LIMA KENTANG GORENG DI PASAR TRADISIONAL DELI TUA DENGAN METODE HPLC (High Performance LiquidChromatography)) - sulasmi, sulasmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
ABSTRACT Background: This study examines acrylamide levels in french fries sold in the traditional market of Deli Tua using the High Performance Liquid Chromatography (HPLC) method. Purpose: is to identify the concentration of acrylamide contained in the samples, as well as provide information regarding the potential health risks associated with the consumption of foods containing the compound. This research Method : is descriptive, carried out in the Quantitative Analysis Chemistry Laboratory, Faculty of Pharmacy, Deli Husada Institute of Health. French fries samples were taken from traders at the Deli Tua traditional market. Acrylamide levels were analyzed using the High Performance Liquid Chromatography (HPLC) method, with procedures including standard solution preparation and measurement using a UV-VIS detector. Results: showed that all the French fries samples analyzed contained acrylamide with varying concentrations. The average acrylamide content in the sample from trader A was 0.7%, while from trader B was 0.5%. These findings show that the acrylamide levels in the fries circulating in the Deli Tua traditional market are not in accordance with the standards set by the Regulation of the Minister of Health. Conclusion: of this study is that the fries sold in the Deli Tua traditional market contain acrylamide with levels that exceed the safe limit. It is recommended to the public to be more careful in choosing fast food, especially french fries. Further research is suggested to use other analysis methods, such as FTIR, with different solvents to obtain more comprehensive results.